Hemoptysis following Talc Pleurodesis in a Pneumothorax Patient - Yusuke Kakiuchi; Fumihiro Yamaguchi; Makoto Hayashi; Yusuke Shikama (Case Reports in Pulmonology)
The purpose of this article is to report a case of hemoptysis occurring in combination with secondary spontaneous pneumothorax following chemical pleurodesis by talc. A Japanese male with cancer of renal pelvis was found with the left pneumothorax and multiple lung metastases. A computed-tomography scan revealed severe emphysema throughout the lungs. Talc pleurodesis was employed to arrest air leakage. The patient developed hemoptysis 45 minutes after talc injection into the thorax. This is the first report of hemoptysis following talc pleurodesis. The agent could induce severe inflammation in capillary vessels of the lung following visceral pleura infiltration.